Effects of prophylactic lidocaine in suspected acute myocardial infarction. An overview of results from the randomized, controlled trials. - MacMahon, S; Collins, R; Peto, R; Koster, R; Yusuf, S (1988)
The effects of prophylactic lidocaine hydrochloride on early ventricular fibrillation and death in patients with suspected acute myocardial infarction were investigated in an overview of 14 randomized trials. During follow-up intervals of one to four hours in the trials of intramuscular lidocaine infusion (6961 patients) and 24 to 48 hours in the trials of intravenous lidocaine injection (2194 patients), a total of 103 cases of ventricular fibrillation and 137 deaths were recorded. Overall, allocation to lidocaine was associated with a reduction in the odds of ventricular fibrillation of about one third, with a 95% confidence interval that ranged from a 3% to a 56% reduction. There was no evidence of any beneficial effect on early mortality; indeed, the odds of early death were about one third greater among patients allocated lidocaine, though this difference was not statistically significant (95% confidence interval, 2% reduction to 95% increase). Because of the small numbers of reported events, the short follow-up periods, and the unavailability of data for some specific causes of death, even an overview of all the trial results does not provide good evidence as to whether prophylactic lidocaine is likely to be helpful or harmful. To answer this question reliably, future trials will need to involve large numbers of patients and prolonged follow-up.